ChemInform Abstract: Nanoarrays: Design, Preparation and Supercapacitor Applications. Issue 35 (September 2015) - Guo, Di; Lai, Linfei; Cao, Anmin; Liu, Huakun; Dou, Shixue; Ma, Jianmin
Abstract Review: 146 refs.